Physical Activity Increases after an Affectively Arousing Daily Life Event - Pollak, Michael H.; Hart, J. Ryan (Frontiers in Psychology, 2017)
Evidence that structured physical activity can help to regulate affective state has spurred interest in identifying associations between unstructured physical activity and affective states during daily life. The present study examined whether stressful daily life situations that elicit affective arousal also elicit increased physical activity in the form of restless movement. The study compared the physical activity of professors (n = 25) after presenting a classroom lecture to their physical activity at the same time of day on a non-lecture workday. The expectation was that lecturing would increase affective arousal, leading to greater restless movement following the lecture compared to the non-lecture control day. The study assessed subjective arousal to confirm that arousal was higher during the lecture. The primary outcome measures were actigraphy-measured standing and stepping times and number of steps and posture transitions. Results indicate that energetic and tense arousal were higher during the lecture than during the control period. Mean (± SE) up time (standing & stepping) for the first minute of the 20 minute post lecture period was double that of the last minute (32.8 ± 5.73 s to 16.5 ± 5.41 s), while it remained low throughout the comparison period on the control day (p = .01). Subjects also took more steps (p = .006) and engaged in more transitions between sitting and standing (p = .02) after the lecture than after the control period. These results support the conclusion that stressful daily life situations that elicit affective arousal also elicit increased physical activity in the form of restless movement and suggest that affective responses to stressful situations may be important determinants of physical activity during daily life.